The Effect of Brand Trust and Brand Image Toward University Selection - Intan Tenisia Prawita Sari; Evi Sylvia (Almana : Jurnal Manajemen dan Bisnis, 2020)
Universities must respond to the competition to attract new students. The purpose of this study was to test and analyze how brand trust and brand image on decision making in university selection at Garut Regency. Descriptive analysis methods are used for responses and path analysis methods are used for the hypothetical test. To test the research instrument is used validity and reliability tests, then to change the data in the ordinal form to interval data using the Method of Successive Interval. The results showed that the respondents' responses indicated that the brand image and brand trust of universities in Garut Regency were very good. Furthermore, the variables of brand trust and brand image have a simultaneous and partial influence on the variable of choosing decisions. Then the variable that had the greatest influence on the decision to choose a campus in Garut Regency was the brand image variable followed by the brand trust variable.